Odpowiedzi

2010-03-05T08:52:17+01:00
(4-2x) - (x+3) = (x-5) + (-3 - x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3+3-4
-3x=-9|*(-1)
3x=9
x=3

(3- 2x) + (3x+4) =- (3-2x) + (5x + 4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-4-3
-6x=-6|*(-1)
6x=6
x=1

2010-03-05T08:55:45+01:00
A)
(4-2x) - (x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x-x+x=-8-4+3
-3x=-9/(-3)
x=3
b)
(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6/(-6)
x=1
Najlepsza Odpowiedź!
2010-03-05T09:56:33+01:00
A)
(4-2x) - (x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x-x+x=-8-4+3
-3x=-9/(-3)
x=3
b)
(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6/(-6)
x=1